Organizational change in educational institutions - Helina Apriyani (Cendikia : Media Jurnal Ilmiah Pendidikan, 2023)
Organizational change is the current state towards the expected future state in the organization. Organizational changes in educational institutions are a sign that organizations must be able to develop. Change is one of the most critical aspects of effective management. Changes in organizations do not always take place smoothly, most face resistance, both from individual, group and organizational levels. Therefore, change needs to be recognized, understood, managed and created to improve performance and achieve expected goals, both by individuals, groups and organizations. Human resources need to be prepared to accept and implement the change themselves. Organizational changes are often needed to stimulate performance and maintain competitiveness and existence within the organization. But sometimes change can trigger resistance challenges within the organization itself. various resources and efforts are needed to suppress possible obstacles that will arise in the future. This research uses qualitative studies and literature in collecting research data. Effective change management involves good communication, involvement of organizational members, monitoring progress, and managing changes in a gradual and planned manner to minimize negative impacts.